2004
DOI: 10.1002/nav.20034
|View full text |Cite
|
Sign up to set email alerts
|

Index policies for the routing of background jobs

Abstract: Arriving (generic) jobs may be processed at one of several service stations, but only when no other (dedicated) jobs are waiting there. We consider the problem of how to route these incoming background jobs to make best use of the spare service capacity available at the stations. We develop an approximative approach to Whittle's proposal for restless bandits to obtain an index policy for routing. The indices concerned are increasing and nonlinear in the station workload. A numerical study testifies to the stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Book length treatments of restless bandits can be found in [26] and [44]. In the particular area of load balancing, there has been several previous works that have applied the restless banding framework, and who have calculated Whittle's index either in closed-form or via an iterative scheme (see [3,6,17,37,39]). For example, in [6], servers are PS and an iterative scheme is reported to compute Whittle's index in the case of linear cost functions and no blocking.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Book length treatments of restless bandits can be found in [26] and [44]. In the particular area of load balancing, there has been several previous works that have applied the restless banding framework, and who have calculated Whittle's index either in closed-form or via an iterative scheme (see [3,6,17,37,39]). For example, in [6], servers are PS and an iterative scheme is reported to compute Whittle's index in the case of linear cost functions and no blocking.…”
Section: Related Literaturementioning
confidence: 99%
“…For example, in [6], servers are PS and an iterative scheme is reported to compute Whittle's index in the case of linear cost functions and no blocking. The load balancing problem in [3,17] deals with FCFS servers with dedicated arrivals for each queue. Dedicated arrivals have priority over new arrivals in the load balancing model of [17].…”
Section: Related Literaturementioning
confidence: 99%
“…See Niño-Mora [10] and Whittle [16]. Glazebrook and Kirkbride [3] have latterly espoused an approach to complex routing problems which is a hybrid of these methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…Further, a range of empirical studies have demonstrated the power and practicability of Whittle's approach in a range of application contexts. See, for example, Ansell et al [2], Opp et al [23], Glazebrook et al [14,15], and Glazebrook and Kirkbride [12,13].…”
mentioning
confidence: 99%
“…We call this problem p n . Plainly, from (12), an optimal policy for (6) and (9) simply runs optimal policies for the p n 1 ≤ n ≤ N , in parallel. We now follow Whittle [30] in requiring structure in optimal policies for each p n that will permit development of an appropriate calibrating function n a b × n → + for bandit n. In order to do this, we write b n u n for the passive set corresponding to policy u n , which is stationary for p n , namely Under (I) and (II), the corresponding index for bandit n n a b × n → + is given by n x n = inf ∈ + x n ∈ b n u n (13) From (13), n x n has an interpretation as a fair charge (per unit of resource) for the additional resource consumed in going from passive (b) to active (a) when bandit n is in state x n .…”
mentioning
confidence: 99%